High Prevalence of Asymptomatic Deep Vein Thrombosis on Admission in a Medical Unit among Elderly Patients - Oger, Emmanuel; Bressollette, Luc; Nonent, Michel; Lacut, Karine; Guias, Bruno; Couturaud, Francis; Leroyer, Christophe; Mottier, Dominique (Thrombosis and Haemostasis, 2002)
The prevention of venous thromboembolism in medical patients remains questioned. All consecutive outpatients admitted in our medical unit were considered for inclusion in this study which aimed to estimate the prevalence of asymptomatic venous thrombosis on admission and the incidence during hospital stay. Exclusion criteria were: age <18 years, suspicion of venous thromboembolism, stay <4 days, ongoing anticoagulant therapy. Venous compression ultrasonography of the lower limbs was performed within 48 h. 234 patients were included. The prevalence of asymptomatic deep vein thrombosis on admission and the incidence during hospital follow-up were respectively 5.5% (95% confidence interval, 3.1 to 9.5%) and 2.6 per 1000 person-days (95% confidence interval, 0.0 to 5.2). The prevalence and the incidence reached respectively 17.8% (95% confidence interval, 8.5 to 32.6%) and 6.0 per 1000 person-days (95% confidence interval, 0.0 to 12.7) among patients over 80 years. A high prevalence of asymptomatic deep vein thrombosis on admission was suggested particularly among elderly medical patients.
Keywords: Venous thrombosis; ultrasonography; elderly; epidemiology